A kind of water-based chitosan / citric acid supramolecular adhesive and its preparation method and application
By developing aqueous chitosan/citric acid supramolecular adhesives, the problems of uncontrollable viscosity, low bonding strength and poor water resistance of bio-based adhesives are solved, and the bonding effect of high strength and water resistance is achieved, which is suitable for bonding of different wooden units.
Patent Information
- Application Number
- CN202310984517.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The existing bio-based adhesives have uncontrollable viscosity, low bonding strength, poor water resistance, and the synthesis process requires energy input and time, so they cannot be used for bonding of different wooden units.
A water-based chitosan/citric acid supramolecular adhesive was developed, prepared by mixing dissolved chitosan and citric acid at room temperature to form a dynamic three-dimensional network structure to achieve controllable viscosity and high-strength bonding.
This adhesive does not require the addition of curing agent, has simple process and high efficiency, can meet the bonding needs of different wooden units, has high strength and water resistance, and meets national standards.
Smart Images

Figure CN117025129B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives. Background Art
[0002] Sustainable bio-based materials composed of wood as the basic unit are closely related to people's lives, such as plywood, particleboard, fiberboard used in furniture, and veneer laminated lumber used in structural buildings. Most of them are composed of both wood and adhesives, but the adhesives used are almost all petroleum-derived resins with formaldehyde as the constituent unit, such as urea-formaldehyde resin, formaldehyde-melamine resin and phenol-formaldehyde resin, which will continuously release formaldehyde and other volatile organic compounds during use. Formaldehyde has been listed as a carcinogen and teratogen by the World Health Organization due to its great harm to the human body. This has forced people to seek safer and more environmentally friendly adhesives. At present, the development of wood adhesives based on natural renewable materials has received great attention, such as soy protein-based adhesives, lignin-based adhesives, starch-based adhesives, etc., which have shown great potential to replace aldehyde resins in the application of artificial boards. However, these bio-based adhesives still have many problems. For example, soy protein, lignin and starch are all high-molecular biomass raw materials. The viscosity of adhesives prepared from these raw materials is often large, greater than 5000mPa·S, and the viscosity is uncontrollable. They are only suitable for the current commercial wood-based board plywood gluing method (roller gluing), and cannot be applied to the particleboard gluing method. The commercial gluing method of particleboard is spray gluing, and the viscosity of the required adhesive needs to be below 1000mPa·S. As a result, the current bio-based adhesives can only be used for the bonding of wood veneer biocomposites, and cannot be used for bonding other non-veneer materials such as wood shavings. In addition, soy protein and starch have weak adhesion, poor water resistance, and poor cohesion. They often need to be chemically modified or blended with current traditional resins such as epoxy resins and polyurethane resins to improve their adhesion and cohesion, which will undoubtedly increase the cost of bio-based adhesives. At the same time, these adhesives require energy input during the preparation process, and most of the synthesis conditions are high temperature for several hours, which runs counter to the current dual-carbon strategy.
[0003] Citric acid is a low-molecular organic acid with abundant reserves in nature. It is widely found in plant fruits, animal bones, muscles, and blood. It has the advantages of being renewable, antiseptic, mildew-resistant, and environmentally friendly. At the same time, citric acid has two active functional groups (carboxyl and hydroxyl), and has excellent adhesion when combined with polar materials (such as wood). It has been used in the gluing of fiberboard and particleboard. However, when citric acid is used as an adhesive, it has low viscosity and can easily penetrate into the porous wood gaps during the gluing process, causing waste and failing to form a continuous adhesive film on the veneer, resulting in low bonding strength and poor water resistance (not resistant to boiling water).
[0004] Chitosan is a product of partial deacetylation of chitin from shrimp shells, crab shells, etc. It has a similar structure to cellulose and is rich in hydroxyl groups. After dissolving, it will re-form abundant hydrogen bonds. At the same time, because chitosan is a high molecular biomass raw material, the molecules will be entangled and the interaction between molecules will be enhanced, which makes the adhesive with it as the main component have a low solid content (<10wt%) and a high viscosity, which is easy to explode when used for single board bonding. Summary of the invention
[0005] The present invention aims to solve the problems of existing bio-based adhesives, such as uncontrollable viscosity, low bonding strength, poor water resistance, long synthesis time and energy input required in the synthesis process, and inability to be used for gluing different wooden units, and provides a water-based chitosan / citric acid supramolecular adhesive and a preparation method and application thereof.
[0006] A water-based chitosan / citric acid supramolecular adhesive consists of 50 to 70 parts of water, 1.5 to 10 parts of chitosan, 10 to 40 parts of citric acid and 0 to 20 parts of filler in parts by mass.
[0007] A method for preparing an aqueous chitosan / citric acid supramolecular adhesive is carried out according to the following steps:
[0008] Weigh 50 to 70 parts of water, 1.5 to 10 parts of chitosan, 10 to 40 parts of citric acid and 0 to 20 parts of filler by mass, and then mix and dissolve them at room temperature to obtain a water-based chitosan / citric acid supramolecular adhesive.
[0009] The invention discloses an application of a water-based chitosan / citric acid supramolecular adhesive, which is used for preparing plywood, veneer laminate, particleboard, fiberboard or blockboard.
[0010] The beneficial effects of the present invention are:
[0011] (1) The main raw materials of the water-based chitosan / citric acid supramolecular adhesive are chitosan, citric acid, and water. The raw materials are non-toxic, the solvent is water, and it is green and environmentally friendly without any formaldehyde added;
[0012] (2) The preparation process of the aqueous chitosan / citric acid supramolecular adhesive is simple. It only has two main components, chitosan and citric acid, which can be prepared by mixing and dissolving. The preparation time is short, the required equipment is very simple, the reaction conditions are mild, and no energy input is required. It is very easy to scale up the operation process and realize industrial production.
[0013] (3) The water-based chitosan / citric acid supramolecular adhesive has a very long trial period. The prepared adhesive has a shelf life of 1 month or more. The boiling water resistance and shear strength of the veneer composite material (plywood) prepared with the adhesive that has been stored for more than 1 month are almost the same as or stronger than those of the plywood prepared with the ready-mixed adhesive.
[0014] (4) No curing agent needs to be added during the bonding process of the water-based chitosan / citric acid supramolecular adhesive for biomass composite materials, and the curing conditions are simple; the water-based chitosan / citric acid supramolecular adhesive for bonding biomass composite materials can completely adopt the traditional liquid sizing process, which is simple, efficient, and particularly easy to mass produce;
[0015] (5) Considering the entire production process, the biomass materials bonded by the water-based chitosan / citric acid supramolecular adhesive are non-toxic and harmless to consumers, industrial producers and the environment. It is a truly healthy and environmentally friendly adhesive that conforms to the principle of atom economy. The finished plywood of the veneer composite material shows that its performance fully meets the requirements of the latest national standard (GB / T9846-2015) Class I and II plywood. The water resistance of the veneer laminated wood composited with it and the veneer can meet the requirements of the national standard (GB / T 20241-2021) for impregnation and peeling of structural veneer laminated wood. The finished particleboard of the non-veneer composite material shows that its performance fully meets the requirements of the latest national standard (GB / T 4897-2015) P5 particleboard. In summary, it breaks the technical limitation that the current bio-based adhesive can only be used for bonding veneer composite materials, and breaks through the technical bottleneck of the current organic solvent formaldehyde bonding mode. A water-based, formaldehyde-free, sustainable and environmentally friendly supramolecular water-based adhesive with great application prospects is provided.
[0016] The invention is used for a water-based chitosan / citric acid supramolecular adhesive and a preparation method and application thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a comparison chart of the insolubility rate of the aqueous chitosan / citric acid supramolecular adhesive film before and after heat treatment in Example 2;
[0018] Figure 2 This is a test diagram of the trial period of the aqueous chitosan / citric acid supramolecular adhesive of Example 2;
[0019] Figure 3 This is a scanning electron microscope image of the dry bonding interface of the three-layer plywood of Example 2;
[0020] Figure 4 This is a scanning electron microscope image of the bonding interface of the three-layer plywood in Example 2 after the aging resistance bonding strength test;
[0021] Figure 5 This is a failure mode diagram of the three-layer plywood after the dry bonding strength test of Example 2;
[0022] Figure 6 This is a failure mode diagram of the three-layer plywood after the aging resistance bonding strength test of Example 2;
[0023] Figure 7 This is a graph showing the test results of the immersion and peeling performance of the six-layer veneer laminate in Example 5;
[0024] Figure 8 This is a graph showing the test results of the impregnation and stripping performance of six-layer veneer laminates in comparative experiment 3;
[0025] Fig. 9 This is a comparison chart of static bending strength of three-layer particleboard of comparative experiment 4 and embodiment 6;
[0026] Fig.10 This is a comparison chart of the internal bonding strength of the three-layer structure particleboard of Experiment 4 and Example 6;
[0027] Fig.11 This is a comparison chart of the 24h water absorption thickness expansion rate of the three-layer structure particleboard of Experiment 4 and Example 6;
[0028] Fig.12 This is a diagram of the failure mode of the three-layer particleboard of Example 6 after the internal bonding strength test. DETAILED DESCRIPTION
[0029] Specific implementation method 1: This implementation method is an aqueous chitosan / citric acid supramolecular adhesive, which is composed of 50 to 70 parts of water, 1.5 to 10 parts of chitosan, 10 to 40 parts of citric acid and 0 to 20 parts of filler in parts by mass.
[0030] The principle is as follows: This specific embodiment develops a novel supramolecular adhesive with controllable viscosity and a dynamic three-dimensional network structure based on supramolecular self-assembly strategy. The adhesive is easy to prepare and is obtained by dissolving chitosan and citric acid in one step under room temperature aqueous conditions.
[0031] Based on the supramolecular self-assembly strategy, this specific implementation method utilizes the characteristics of chitosan and citric acid, and cleverly regulates the compounding ratio of the two to prepare a new supramolecular adhesive with controllable viscosity. In the new supramolecular adhesive, the protonated amino groups of chitosan form ionic crosslinks with the carboxylate ions of citric acid. At the same time, the hydroxyl groups in the chitosan and citric acid molecules also associate hydrogen bonds to coordinate the supramolecular self-assembly process and form a dynamic three-dimensional network structure. The new supramolecular adhesive has suitable viscosity and good film-forming properties. The film can be quickly cured after heating. The dynamic three-dimensional network structure is transformed into a stable three-dimensional network structure and forms an insoluble thermosetting resin. After being treated with boiling water for four hours, the insolubility rate can reach more than 80%, and the cured resin has high water resistance. Biocomposites (such as plywood, veneer laminates, particleboard, etc.) made using this new supramolecular adhesive also have high water resistance. For example, the water resistance of plywood composited with it and veneer can meet the highest level of weather resistance (type I and II plywood) requirements of national standard GB / T 9846-2015; the water resistance of veneer laminates composited with it and veneer can meet the requirements of impregnation and peeling of veneer laminates for structures of national standard GB / T 20241-2021; the water resistance of three-layer particleboard composited with it and coarse and fine shavings can meet the requirements of ordinary particleboard (type P5) used in wet conditions of national standard GB / T4897-2015. This new adhesive solves the problems of low viscosity, weak bonding strength and low water resistance when citric acid is used as an adhesive, and also solves the problems of low solid content, high viscosity and explosive board when chitosan is used as an adhesive. In addition, it also solves the problem that current bio-based adhesives cannot be used to bond different wooden units, and broadens the application of bio-based adhesives in high-performance biomass composite materials. The raw materials of this adhesive are environmentally friendly and renewable, the only solvent used is aqueous solution, and the synthesis process is low-carbon and environmentally friendly. The biomass composite materials manufactured and used using this adhesive can completely avoid the hazards of free formaldehyde and VOCs. It is a new type of high-performance, environmentally friendly and water-resistant adhesive for biomass composite materials, and has broad application prospects.
[0032] The beneficial effects of this specific implementation are:
[0033] (1) The main raw materials of the water-based chitosan / citric acid supramolecular adhesive are chitosan, citric acid, and water. The raw materials are non-toxic, the solvent is water, and it is green and environmentally friendly without any formaldehyde added;
[0034] (2) The preparation process of the aqueous chitosan / citric acid supramolecular adhesive is simple. It only has two main components, chitosan and citric acid, which can be prepared by mixing and dissolving. The preparation time is short, the required equipment is very simple, the reaction conditions are mild, and no energy input is required. It is very easy to scale up the operation process and realize industrial production.
[0035] (3) The water-based chitosan / citric acid supramolecular adhesive has a very long trial period. The prepared adhesive has a shelf life of 1 month or more. The boiling water resistance and shear strength of the veneer composite material (plywood) prepared with the adhesive that has been stored for more than 1 month are almost the same as or stronger than those of the plywood prepared with the ready-mixed adhesive.
[0036] (4) No curing agent needs to be added during the bonding process of the water-based chitosan / citric acid supramolecular adhesive for biomass composite materials, and the curing conditions are simple; the water-based chitosan / citric acid supramolecular adhesive for bonding biomass composite materials can completely adopt the traditional liquid sizing process, which is simple, efficient, and particularly easy to mass produce;
[0037] (5) Considering the entire production process, the biomass materials bonded by the water-based chitosan / citric acid supramolecular adhesive are non-toxic and harmless to consumers, industrial producers and the environment. It is a truly healthy and environmentally friendly adhesive that conforms to the principle of atom economy. The finished plywood of the veneer composite material shows that its performance fully meets the requirements of the latest national standard (GB / T9846-2015) Class I and II plywood. The water resistance of the veneer laminated wood composited with it and the veneer can meet the requirements of the national standard (GB / T 20241-2021) for impregnation and peeling of structural veneer laminated wood. The finished particleboard of the non-veneer composite material shows that its performance fully meets the requirements of the latest national standard (GB / T 4897-2015) P5 particleboard. In summary, it breaks the technical limitation that the current bio-based adhesive can only be used for bonding veneer composite materials, and breaks through the technical bottleneck of the current organic solvent formaldehyde bonding mode. A water-based, formaldehyde-free, sustainable and environmentally friendly supramolecular water-based adhesive with great application prospects is provided.
[0038] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the water is one or a combination of tap water, mineral water, spring water, distilled water, purified water, deionized water, ultrapure water and industrial water. The rest is the same as specific implementation method 1.
[0039] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the relative molecular weight of the chitosan is ≥ 600, and the degree of deacetylation is ≥ 50%. Other aspects are the same as specific implementation method 1 or 2.
[0040] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the citric acid is one of edible citric acid, industrial citric acid, anhydrous citric acid and citric acid monohydrate, or a combination of several thereof. The rest is the same as specific embodiments 1 to 3.
[0041] Specific implementation mode 5: This implementation mode is different from specific implementation modes 1 to 4 in that the filler is one or a combination of montmorillonite and kaolin. The rest is the same as specific implementation modes 1, 2 to 4.
[0042] Specific embodiment 6: This embodiment is a method for preparing an aqueous chitosan / citric acid supramolecular adhesive, which is carried out according to the following steps:
[0043] Weigh 50 to 70 parts of water, 1.5 to 10 parts of chitosan, 10 to 40 parts of citric acid and 0 to 20 parts of filler by mass, and then mix and dissolve them at room temperature to obtain a water-based chitosan / citric acid supramolecular adhesive.
[0044] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that the solid content of the aqueous chitosan / citric acid supramolecular adhesive is 30 wt% to 50 wt%. Other aspects are the same as specific embodiment 6.
[0045] Specific implementation method eight: This implementation method is an application of an aqueous chitosan / citric acid supramolecular adhesive, which is used for the preparation of plywood, veneer laminate, particleboard, fiberboard or blockboard.
[0046] The wood species of the board in this specific implementation method is not limited, and it can be any combination of one or more of coniferous wood, broad-leaved wood, bamboo, or other trees; the type of shavings is not limited, and it can be any combination of one or more of coniferous wood, broad-leaved wood, bamboo, or other plants such as straw.
[0047] Specific embodiment 9: This embodiment is different from specific embodiment 8 in that it is used for the preparation of plywood, veneer laminated wood or particle board, and is carried out according to the following steps:
[0048] When preparing plywood or veneer laminated timber, the glue application rate per unit area is 100g / m 2 ~600g / m 2 Under the conditions of single-sided or double-sided glue coating, and then assembling, pre-pressing after assembling, and then hot pressing for 30s / mm~180s / mm at a hot pressing temperature of 120℃~230℃ and a hot pressing pressure of 0.5MPa~2MPa;
[0049] When preparing particleboard, the blanks are assembled after spraying glue, and then pre-pressed, and then hot pressed for 30s / mm to 180s / mm at a hot pressing temperature of 180°C to 230°C and a hot pressing pressure of 2.2MPa to 4MPa; the glue application amount of the sprayed glue is 4% to 20% of the solid mass of the adhesive to the absolute dry mass of the wood particles. The rest is the same as the eighth embodiment.
[0050] In this specific implementation manner, the hot pressing is 30s / mm to 180s / mm, which specifically means hot pressing is 30s to 180s at a unit thickness of 1mm.
[0051] Specific embodiment 10: This embodiment is different from specific embodiment 8 or 9 in that: when preparing plywood or veneer laminate, the pre-pressing is performed at room temperature and the pre-pressing pressure is 0.5MPa to 1MPa for ≥30min; when preparing particleboard, the pre-pressing is performed at room temperature and the pre-pressing pressure is 0.5MPa to 1MPa for 10s to 60s. The rest is the same as specific embodiment 8 or 9.
[0052] The following examples are used to verify the beneficial effects of the present invention:
[0053] Embodiment 1:
[0054] A water-based chitosan / citric acid supramolecular adhesive consists of 50 parts of water, 10 parts of chitosan and 40 parts of citric acid by mass.
[0055] The water is distilled water.
[0056] The relative molecular weight of the chitosan is 600,000, and the deacetylation degree is 85%.
[0057] The citric acid is citric acid monohydrate.
[0058] The preparation method of the above-mentioned aqueous chitosan / citric acid supramolecular adhesive is carried out according to the following steps:
[0059] 50 parts of water, 10 parts of chitosan and 40 parts of citric acid were weighed by mass, and then mixed and dissolved at room temperature to obtain a water-based chitosan / citric acid supramolecular adhesive.
[0060] The water-based chitosan / citric acid supramolecular adhesive has a solid content of 50 wt % and a viscosity of 72500 mPa·s.
[0061] Embodiment 2: This embodiment is different from Embodiment 1 in that: a water-based chitosan / citric acid supramolecular adhesive is composed of 70 parts of water, 4 parts of chitosan and 26 parts of citric acid by mass. The rest is the same as Embodiment 1.
[0062] The water-based chitosan / citric acid supramolecular adhesive has a solid content of 30 wt % and a viscosity of 14700 mPa·s.
[0063] Embodiment 3: This embodiment is different from Embodiment 1 in that: a water-based chitosan / citric acid supramolecular adhesive is composed of 70 parts of water, 2 parts of chitosan and 28 parts of citric acid by mass. The rest is the same as Embodiment 1.
[0064] The water-based chitosan / citric acid supramolecular adhesive has a solid content of 30 wt % and a viscosity of 467 mPa·s.
[0065] Comparative Experiment 1: This embodiment is different from the first embodiment in that: a citric acid-based adhesive is composed of 70 parts of water and 30 parts of citric acid by mass. The rest is the same as the first embodiment.
[0066] The citric acid-based adhesive has a solid content of 30 wt % and a viscosity of 2.4 mPa·s.
[0067] Comparative Experiment 2: This embodiment differs from the first embodiment in that: a chitosan-based adhesive is composed of 96 parts of water, 3 parts of chitosan and 1 part of acetic acid by mass. The rest is the same as the first embodiment.
[0068] The acetic acid is glacial acetic acid with a mass percentage of 99.5%;
[0069] The chitosan-based adhesive has a solid content of 4wt% and a viscosity of 865mPa·s.
[0070] Embodiment 1:
[0071] The plywood was prepared using the aqueous chitosan / citric acid supramolecular adhesive prepared in Example 2, specifically by the following steps:
[0072] The peeled poplar veneer was dried at room temperature until the moisture content was 7%, and the glue coating amount per unit area was 280g / m 2 Under the conditions of , double-sided glue is applied to obtain a core board with glue applied. The face plate and the core board with glue applied are assembled in a cross-texture manner. After assembly, the face plate is placed in a pre-pressing machine and pre-pressed for 6 hours at room temperature and a pressure of 0.5 MPa to obtain a preheated and pressed board. The preheated and pressed board is placed in a hot press and hot pressed for 80s / mm at a hot pressing temperature of 170°C and a hot pressing pressure of 1 MPa to obtain a three-layer plywood.
[0073] Example 2: This example is different from Example 1 in that plywood is prepared using the aqueous chitosan / citric acid supramolecular adhesive prepared in Example 1, and hot pressing is performed at a temperature of 160° C. and a pressure of 1 MPa for 120 s / mm. Other aspects are the same as in Example 1.
[0074] Embodiment 3: This embodiment is different from Embodiment 1 in that the hot pressing temperature is 180°C and the hot pressing pressure is 1 MPa, and the hot pressing is performed for 30 s / mm. The other conditions are the same as those of Embodiment 1.
[0075] Embodiment 4: This embodiment differs from Embodiment 1 in that the hot pressing temperature is 170°C and the hot pressing pressure is 1 MPa, and the hot pressing is performed for 30 s / mm. The other conditions are the same as those of Embodiment 1.
[0076] Comparative Experiment 1: This comparative experiment is different from Example 1 in that the plywood is prepared with the citric acid-based adhesive prepared in Comparative Experiment 1; the hot pressing is performed at a temperature of 200°C and a pressure of 1 MPa for 30 s / mm. Other aspects are the same as Example 1.
[0077] Comparative Experiment 2: This comparative experiment differs from Example 1 in that the plywood is prepared using the chitosan-based adhesive prepared in Comparative Experiment 2; the hot pressing is performed at a temperature of 200°C and a pressure of 1 MPa for 30 s / mm. Other aspects are the same as Example 1.
[0078] Embodiment 5:
[0079] The aqueous chitosan / citric acid supramolecular adhesive prepared in Example 2 is used to prepare the veneer laminated material, specifically according to the following steps:
[0080] The peeled poplar veneer was dried at room temperature until the moisture content was 7%, and the glue coating amount per unit area was 400g / m 2 Under the conditions of single-sided or double-sided glue coating, a core board with glue coating is obtained, the face plate and the core board with glue coating are assembled in a manner in which the textures are parallel, and the assembly is followed by placing them in a pre-pressing machine, and pre-pressing them for 6 hours at room temperature and a pressure of 0.5 MPa to obtain a preheated and pressed board, and the preheated and pressed board is placed in a hot press, and hot-pressed for 54 s / mm at a hot-pressing temperature of 180°C and a hot-pressing pressure of 1 MPa to obtain a six-layer veneer laminate.
[0081] Comparative Experiment 3: This comparative experiment is different from Example 5 in that the veneer laminate is prepared using the citric acid-based adhesive prepared in Comparative Experiment 1. Others are the same as Example 5.
[0082] Embodiment 6:
[0083] The particleboard was prepared using the aqueous chitosan / citric acid supramolecular adhesive prepared in Example 3, specifically by the following steps:
[0084] The cut poplar wood shavings are placed in a drying oven at 80°C and dried to a moisture content of 5%. After spraying glue, the upper and lower surfaces are paved with fine shavings and the middle is paved with coarse shavings for assembly. After assembly, the shavings are placed in a pre-pressing machine and pre-pressed for 30 seconds at room temperature and a pressure of 0.5MPa to obtain a pre-pressed slab. The pre-pressed slab is placed in a hot press and hot-pressed for 180s / mm at a hot-pressing temperature of 180°C and a hot-pressing pressure of 3MPa to obtain a three-layer particleboard. The amount of glue applied during the spraying glue is 8% of the solid mass in the adhesive to the absolute dry mass of the shavings. The size of the coarse wood shavings is: length 15mm-45mm, width 3mm-10mm, thickness 0.4mm-0.7mm; the size of the fine wood shavings is: length 3mm-15mm, width 0.5mm-1.5mm, thickness 0.2mm-0.4mm.
[0085] Comparative Experiment 4: This comparative experiment is different from Example 6 in that the particleboard is prepared with the citric acid-based adhesive prepared in Comparative Experiment 1. The rest is the same as Example 6.
[0086] The solid content test of the adhesive in Examples 1 to 3 and Comparative Experiments 1 and 2 was conducted in accordance with the requirements of the national standard GBT14074-2006; the viscosity test was conducted in accordance with the national standard GB / T2794-1995.
[0087] The aqueous chitosan / citric acid supramolecular adhesive of Example 2 was spread on a plastic culture dish by a casting method and dried at room temperature to form a film, i.e., an unheat-treated film. The unheat-treated film was dried in a drying oven at 170° C. until the mass was constant, to obtain a heat-treated film.
[0088] The insolubility rate of the film is determined as follows:
[0089] The initial mass of the film is recorded as m0, and then the film is placed in 100℃ boiling water for 4h, and then the boiled film is dried in a 63℃ oven until the mass is stable and the final mass is recorded as m1. Each film is tested 3 times and the average value is taken. The insolubility rate is calculated as follows:
[0090]
[0091] Figure 1 This is a comparison chart of the insolubility of the water-based chitosan / citric acid supramolecular adhesive film of Example 2 before and after heat treatment; as can be seen from the figure, the film solidifies after heating, and the dynamic three-dimensional network structure is transformed into a stable three-dimensional network structure. After four hours of boiling water treatment, the insolubility rate can reach more than 80%. The insolubility rate of the film before heat treatment is 0%, and the insolubility rate of the film after heat treatment is 87.03±0.75%.
[0092] The performance indicators of plywood are determined as follows:
[0093] Glue shear strength test: Tested with reference to GB / T17657-2013 standard. Test specimens were prepared according to GB / T17657-2013 standard. When preparing test specimens, the wood grain direction of the core board between the glue layers to be tested should be perpendicular to the length direction of the test specimens. The slot width and depth of the test specimens were carried out in accordance with the illustrated dimensions and requirements drawn according to the national standard. According to GB / T17657-2013 standard, the prepared standard test specimens were stored in a desiccator for 2 days. The test was conducted using a universal mechanical testing machine (RGT-20), with a force sensor of 50KN and a tensile speed of 5mm / min.
[0094] Dry bonding strength: The prepared standard specimens are directly subjected to tensile shear tests without any treatment.
[0095] Wet bonding strength: According to GB / T17657-2013 standard, the prepared standard specimens were immersed in hot water at 63°C for 3 hours, cooled at room temperature for 10 minutes, and then subjected to tensile shear tests.
[0096] Aging resistance bonding strength: According to GB / T17657-2013 standard, the prepared standard specimens are immersed in boiling water for 4 hours, then dried in a forced air drying oven at (60±3)℃ for 16h~20h, immersed in boiling water for 4h, and then placed in cold water at a temperature below 30℃ for at least 1h before conducting tensile shear tests.
[0097] From Example 1 and Example 2 in Table 1, it can be seen that the finished plywood of the veneer composite material produced by the adhesive fully meets the requirements of the latest national standard (GB / T 9846-2015) Class I and Class II plywood. Class II plywood requires a wet bonding strength of ≥0.7 MPa, and Class I plywood requires an aging resistance bonding strength of ≥0.7 MPa.
[0098] Table 1. Dry, wet bonding strength and aging resistance bonding strength of three-layer plywood
[0099]
[0100] The aqueous chitosan / citric acid supramolecular adhesive of Example 2 was stored at room temperature for 1 month, and plywood was prepared according to Example 1 using the adhesive stored for 1 month, and the aging resistance bonding strength was tested. Figure 2 shown. Figure 2 This is a test diagram of the trial period of the aqueous chitosan / citric acid supramolecular adhesive of Example 2; as can be seen from the figure, the trial period of the aqueous chitosan / citric acid supramolecular adhesive is very long, and the aging-resistant bonding strength of the plywood prepared according to Example 1 using the adhesive that has been stored for one month is stronger than that of the plywood prepared using the freshly prepared adhesive.
[0101] Figure 3This is a scanning electron microscope image of the dry bonding interface of the three-layer plywood in Example 2; it can be seen from the figure that the adhesive forms a continuous film at the interface of the two wood units, indicating that the film of the adhesive has film-forming properties, and at the same time, it quickly solidifies after heating to form a stable resin, and forms a mechanical interlocking structure with the hierarchical porous structure of the wood.
[0102] Figure 4 This is a scanning electron microscope image of the bonding interface after the aging resistance bonding strength test of the three-layer plywood in Example 2; it can be seen from the figure that the continuous adhesive film did not dissolve after the aging treatment and still maintained the original mechanical interlocking structure. At the same time, it was found that under the condition that the wood cell wall was damaged in many places, the bonding interface remained in a closed state, indicating that the adhesive formed an effective bond with the wood unit.
[0103] Figure 5 This is a failure mode diagram of the three-layer plywood in Example 2 after the dry bonding strength test; it can be seen from the figure that the strength of the resin body cured by the adhesive is higher than the strength of the wood.
[0104] Figure 6 This is a failure mode diagram of the three-layer plywood of Example 2 after the aging resistance bonding strength test; it can be seen from the figure that the body strength of the resin cured by the adhesive is still higher than the strength of the wood after aging treatment.
[0105] The performance indicators of laminated veneer lumber are determined as follows:
[0106] Immersion stripping performance test: The test is carried out in accordance with GB / T20241-2021 standard.
[0107] (1) Cold water immersion stripping:
[0108] Immerse the specimens in 25℃ water for 24h, take them out and place them in a drying oven at (70±3)℃ to dry them until the mass of the specimens is within 105% of the mass before the test. Observe and measure the ratio of the peeling length of the four sides of all adhesive layers to the total length of all adhesive layers, and the ratio of the peeling length of any adhesive layer to the sum of the four sides of the adhesive layer.
[0109] (2) Boiling and immersion peeling:
[0110] Immerse the specimens in boiling water for 4 hours, take them out and immerse them in 25℃ water for 1 hour, and then dry them in a drying oven at (70±3)℃ until the mass of the specimens is within 105% of the mass before the test. Observe and measure the ratio of the peeling length of the four sides of all adhesive layers to the total length of all adhesive layers, and the ratio of the peeling length of any adhesive layer to the sum of the four sides of the adhesive layer.
[0111] Figure 7This is the test result of the immersion stripping performance of the six-layer veneer laminated timber in Example 5; it can be seen from the figure that after the cold water immersion stripping, the ratio of the peeling glue lines on the four sides of all the adhesive layers to the total length of all the adhesive layers and the ratio of the peeling length of any adhesive layer to the sum of the four sides of the adhesive layer are both 0%, and at the same time, after the boiling water immersion stripping, the ratio of the peeling glue lines on the four sides of all the adhesive layers to the total length of all the adhesive layers and the ratio of the peeling length of any adhesive layer to the sum of the four sides of the adhesive layer are also 0%. It meets the requirements of the national standard GB / T 20241-2021 for immersion stripping of structural veneer laminated timber.
[0112] Figure 8 This is a graph showing the test results of the six-layer veneer laminated timber impregnation and stripping performance in comparison experiment 3; it can be seen from the figure that after the six-layer veneer laminated timber is impregnated and stripped by cold water, the ratio of the peeling glue lines on the four sides of all glue layers to the total length of all glue layers and the ratio of the peeling length of any glue layer to the sum of the four sides of the glue layer are both 100%. At the same time, after the six-layer veneer laminated timber is impregnated and stripped by boiling water, the ratio of the peeling glue lines on the four sides of all glue layers to the total length of all glue layers and the ratio of the peeling length of any glue layer to the sum of the four sides of the glue layer are also 100%, which does not meet the requirements of the national standard GB / T 20241-2021 for impregnation and stripping of structural veneer laminated timber.
[0113] The performance indicators of particleboard are determined as follows:
[0114] (1) Static bending strength test: The specimens were prepared and tested according to the national standard GB / T17657-2013. The specimen size was 150 mm × 50 mm, and the span was 100 mm. The force sensor was 50 KN, and the loading speed was 5 mm / min.
[0115] (2) Internal bonding strength test: The specimens were prepared and tested according to the national standard GB / T17657-2013. The specimen size was 50 mm × 50 mm. The adhesive used between the specimen and the fixture was hot melt adhesive. According to the GB / T17657-2013 standard, the prepared bonding specimens were placed in a balanced treatment room at a temperature of (20 ± 2) °C and a relative humidity of (65 ± 5)%. The test should be completed within 1 hour after the specimens were taken out of the balanced treatment room. The force sensor was 50 KN and the tensile speed was 5 mm / min.
[0116] (3) 24h water absorption thickness expansion rate: The specimens were prepared and tested according to the national standard GB / T17657-2013. The specimen size was 50mm×50mm, and the water used was tap water with a pH of 7±1. The temperature was 20±1℃, and the specimens were immersed in a water tank, which remained constant during the test. The surface of the specimens was perpendicular to the water surface. There was at least 15mm between the specimens and between the specimens and the bottom and wall of the water tank. The upper part of the specimen was (25±5)mm below the water surface.
[0117] Fig. 9 The static bending strength comparison chart of the three-layer structure particleboard of comparative experiment 4 and embodiment 6; it can be seen from the figure that the static bending strength of the three-layer structure particleboard of comparative experiment 4 is 8.84±2.50MPa, which is lower than the static bending strength ≥13MPa requirement of the national standard GB / T 4897-2015 for ordinary particleboard (P5 type) used in a wet state. The static bending strength of the three-layer structure particleboard of embodiment 6 is 15.71±0.83MPa, which is higher than the static bending strength ≥13MPa requirement of the national standard GB / T 4897-2015 for ordinary particleboard (P5 type) used in a wet state.
[0118] Fig.10 The internal bonding strength comparison diagram of the three-layer structure particleboard of comparative experiment 4 and embodiment 6; it can be seen from the figure that the internal bonding strength of the three-layer structure particleboard of comparative experiment 4 is 0.19±0.90MPa, which is lower than the internal bonding strength ≥0.30MPa requirement of the national standard GB / T 4897-2015 for ordinary particleboard (P5 type) used in a humid state. The internal bonding strength of the three-layer structure particleboard of embodiment 6 is 1.16±0.27MPa, which is higher than the internal bonding strength ≥0.3MPa requirement of the national standard GB / T 4897-2015 for ordinary particleboard (P5 type) used in a humid state.
[0119] Fig.11 The 24h water absorption thickness expansion rate comparison chart of the three-layer structure particleboard of comparative experiment 4 and embodiment 6; it can be seen from the figure that the 24h water absorption thickness expansion rate of the three-layer structure particleboard of comparative experiment 4 is 29.43±6.04%, which does not meet the requirement of the national standard GB / T 4897-2015 that the 24h water absorption thickness expansion rate of the ordinary particleboard (P5 type) used in a humid state is ≤23%. The 24h water absorption thickness expansion rate of the three-layer structure particleboard of embodiment 6 is 19.90±2.42%, which is higher than the requirement of the national standard GB / T4897-2015 that the 24h water absorption thickness expansion rate of the ordinary particleboard (P5 type) used in a humid state is ≤23%.
[0120] Fig.12 This is a failure mode diagram of the three-layer structure particleboard of Example 6 after the internal bonding strength test; as can be seen from the figure, the failure mode of the particleboard is multiple wood failures, indicating that the resin strength of the adhesive after curing is higher than the body strength of the wood particles.
Claims
1. A water-based chitosan / citric acid supramolecular adhesive, characterized in that The method is prepared by mixing and dissolving 50 to 70 parts of water, 2 to 10 parts of chitosan, 26 to 40 parts of citric acid and 0 to 20 parts of filler at room temperature. The relative molecular weight of the chitosan is ≥ 600,000, and the degree of deacetylation is ≥ 85%; The solid content of the aqueous chitosan / citric acid supramolecular adhesive is 30wt%-50wt% and the viscosity is 467mPa·s-72500mPa·s.
2. The aqueous chitosan / citric acid supramolecular adhesive according to claim 1, characterized in that The water is one of tap water, mineral water, spring water, distilled water, purified water, deionized water, ultrapure water and industrial water, or a combination of several of them.
3. The aqueous chitosan / citric acid supramolecular adhesive according to claim 1, characterized in that The citric acid is one of edible citric acid, industrial citric acid, anhydrous citric acid and citric acid monohydrate, or a combination of several of them.
4. The aqueous chitosan / citric acid supramolecular adhesive according to claim 1, characterized in that The filler is one of montmorillonite and kaolin or a combination of the two.
5. The use of an aqueous chitosan / citric acid supramolecular adhesive as claimed in claim 1, characterized in that It is used in the preparation of plywood, laminated veneer lumber, particleboard, fiberboard or blockboard.
6. The use of an aqueous chitosan / citric acid supramolecular adhesive according to claim 5, characterized in that It is used in the preparation of plywood, laminated veneer lumber or particle board in the following steps: When preparing plywood or veneer laminated timber, the glue application rate per unit area is 100g / m 2 ~600g / m 2 Under the conditions of single-sided or double-sided glue coating, and then assembling, pre-pressing after assembling, and then hot pressing for 30s / mm~180s / mm at a hot pressing temperature of 120℃~230℃ and a hot pressing pressure of 0.5MPa~2MPa; When preparing particleboard, the particles are assembled after spraying glue, and then pre-pressed, and then hot pressed for 30s / mm to 180s / mm at a hot pressing temperature of 180°C to 230°C and a hot pressing pressure of 2.2MPa to 4MPa; the amount of glue applied by spraying glue is 4% to 20% of the solid mass of the adhesive to the absolute dry mass of the particles.
7. The use of an aqueous chitosan / citric acid supramolecular adhesive according to claim 5, characterized in that When preparing plywood or veneer laminated timber, the pre-pressing is performed at room temperature and a pre-pressing pressure of 0.5MPa to 1MPa for ≥30min; when preparing particleboard, the pre-pressing is performed at room temperature and a pre-pressing pressure of 0.5MPa to 1MPa for 10s to 60s.
Citation Information
Patent Citations
Plant-based polyester polyol-chitosan adhesive, and preparation method and application thereof
CN103320078A